Выявление критических условий вырожденно-разветвленных цепных реакций численным методом - Л. А. Тавадян; А. А. Хачоян; Г. А. Мартоян (ՀՀ ԳԱԱ հրատ.)
Предложен численный метод выявления и анализа критических явлений в вырожденно– разветвленных цепных реакциях, основанный на гамильтоновской систематизации кинетических моделей этих реакций. В качестве критерия критического состояния реакционной системы выбрано экстремальное поведение функции, описывающей суммарную концентрацию исходных и промежуточных компонентов реакций. Առաջարկվել է կինետիկական մոդելների համիլտոնիան համակարգման վրա հիմնված այլասերված ճյուղավորումներով ընթացող ռեակցիաների սահմանային վիճակների բացահայտման եղանակ: Հաշվարկները կատարելու համար որպես կրիտիկական վիճակի չափանիշ ընտրվել է ելային և միջանկյալ նյութերի գումարային կոնցենտրացիան նկարագրող ֆուկցիայի էքստրեմալության պայմանը: A numerical method of revelation and analysis of critical conditions in chain branching reactions, based on Hamiltonian systematization of reactions’ kinetic models has been suggested. The extremum behavior of the function describing summary concentration of initial and intermediate components is chosen as a criteria for critical conditions of the reaction system. The critical conditions are such conditions when the induction period of reaction dramatically increased with a small increase of initial concentration of inhibitor. The base of present method is Hamiltonian systematization of kinetic models of chemical reactions.
Keywords: Physical Chemistry